Bad feminist: essays - Gay, Roxane (Harper Perennial, 2014)
In these funny and insightful essays, Gay takes us through the journey of her evolution as a woman (Sweet Valley High) of color (The Help) while also taking readers on a ride through culture of the last few years (Girls, Django in Chains) and commenting on the state of feminism today (abortion, Chris Brown). The portrait that emerges is not only one of an incredibly insightful woman continually growing to understand herself and our society, but also one of our culture.Bad Feminist is a sharp, funny, and spot-on look at the ways in which the culture we consume becomes who we are, and an inspiring call-to-arms of all the ways we still need to do better, coming from one of our most interesting and important cultural critics.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; cours; culture populaire; cycles supérieurs; discipline; fem1000; fem7000; genre; identités LGBTQIA2+; lit2815; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; témoignage; états-unis; études littéraires